Synthesis and Structural Characterization of β‐Ketoiminate‐Stabilized Gallium Hydrides for Chemical Vapor Deposition Applications. Issue 33 (17th July 2014) - Marchand, Peter; Pugh, David; Parkin, Ivan P.; Carmalt, Claire J.
Abstract Bis‐β‐ketoimine ligands of the form [(CH2)n{N(H)C(Me)CHC(Me)O}2] (LnH2, n=2, 3 and 4) were employed in the formation of a range of gallium complexes [Ga(Ln)X] (X=Cl, Me, H), which were characterised by NMR spectroscopy, mass spectrometry and single‐crystal X‐ray diffraction analysis. The β‐ketoimine ligands have also been used for the stabilisation of rare gallium hydride species [Ga(Ln)H] (n=2 (7); n=3 (8)), which have been structurally characterised for the first time, confirming the formation of five‐coordinate, monomeric species. The stability of these hydrides has been probed through thermal analysis, revealing stability at temperatures in excess of 200 °C. The efficacy of all the gallium β‐ketoiminate complexes as molecular precursors for the deposition of gallium oxide thin films by chemical vapour deposition (CVD) has been investigated through thermogravimetric analysis and deposition studies, with the best results being found for a bimetallic gallium methyl complex [L3{GaMe2}2] (5) and the hydride [Ga(L3)H] (8). The resulting films (F5 and F8, respectively) were amorphous as‐deposited and thus were characterised primarily by XPS, EDXA and SEM techniques, which showed the formation of stoichiometric (F5) and oxygen‐deficient (F8) Ga2O3 thin films.